PENATAAN PEDAGANG KAKI LIMA DI BATU KAJANG KALIMANTAN TIMUR - Milianti, Maya; Octaviana, Anna (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
The existence of public open spaces that accommodates people's social activities in Paser Regency, especially in Batu Kajang, is very minimal. The lack of intensity of land for productive open spaces that is economically profitable for street vendors has an impact on the emergence of street vendors that sell along the side of the road in Batu Kajang. The impact of the existence of the street vendor caused the traffic jam. Therefore, to anticipate such conditions, open spaces area that can accommodate the selling activities of street vendors are needed. The method used is architectural programming which is a process of gathering information, analyzing, and making recommendations for the success of the design. In this case, the concept applied to the design area is placemaking which is a form of space through human interaction with buildings and building interactions with the environment.